2021
DOI: 10.1063/5.0046699
|View full text |Cite
|
Sign up to set email alerts
|

Fast and robust exciton preparation in a coupled semiconductor quantum dot–metal nanoparticle system using shortcuts to adiabaticity

Abstract: We study the efficient preparation of the exciton state in a hybrid nanostructure composed by a semiconductor quantum dot and a metallic nanoparticle, when starting from the ground state, using pulses derived with the method of shortcuts to adiabaticity. We show with numerical simulations that high levels of exciton population can be obtained for a wide range of interparticle distances and for short pulse durations. This behavior appears also to be robust against small positioning errors of the system. The fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…An active research topic within the field of quantum plasmonics [ 1 , 2 ] is the efficient population control of the exciton and biexciton states in semiconductor quantum dots (SQD) closely placed to metallic nanoparticles (MNP) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An active research topic within the field of quantum plasmonics [ 1 , 2 ] is the efficient population control of the exciton and biexciton states in semiconductor quantum dots (SQD) closely placed to metallic nanoparticles (MNP) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A great portion of studies in this area is devoted to population transfer between the ground and single exciton states of the SQD, using external fields and with the MNP present [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 , 14 , 16 ]. In many of these works it is reported that the MNP substantially modifies the period of Rabi oscillations between these states [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], which can even be destroyed for specific SQD-MNP distances [ 4 , 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current studies in photonics, coupled structures formed from semiconductor quantum dots and metal particles at the nanoscale play an important role as they give, in many cases, enhanced optical properties in comparison to individual SQDs and MNPs [1]. The coupling of the excitons to plasmons is responsible for the emergence of interesting optical effects from the SQD-MNP structures, including altered excitonic Rabi oscillations [2][3][4], creation and control of optical bistability and multistability [5][6][7][8][9], population transfer to the exciton [10][11][12][13][14] or biexciton state with high accuracy [15][16][17], controlled slow light [18], creation of gain without inversion [19][20][21], strong enhancement of second harmonic generation [22], and strong modification of four-wave mixing, as well as self-or cross-Kerr nonlinearity [23][24][25][26], control of resonance fluorescence [27][28][29][30], and several others [31][32][33][34][35][36][37][38]. These effects can find applications in the construction of efficient optical devices which can be implemented in the fields of nanophotonics and quantum technology.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the fidelity is also reduced when the biexciton binding energy assumes larger values and the pulses become longer. We point out that in our recent work [39] we successfully used transitionless quantum driving for the efficient transfer of population form the ground to the exciton state of a SQD placed next to a MNP.…”
Section: Introductionmentioning
confidence: 99%